2015
DOI: 10.1002/alr.21598
|View full text |Cite
|
Sign up to set email alerts
|

Nasal nitric oxide as a marker of sinus mucosal health in patients with nasal polyposis

Abstract: This is the first study to show that nNO levels may be a marker of sinus mucosal health following ESS in patients with polyps. This has important implications for nNO in its potential etiologic role in mediating ongoing sinus inflammation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
37
0
2

Year Published

2015
2015
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 38 publications
(42 citation statements)
references
References 31 publications
(33 reference statements)
2
37
0
2
Order By: Relevance
“…They found significantly lower levels of nNO in patients with CRSwNP compared to that in patients with CRSsNP and controls. Conversely, nNO concentrations increased significantly in patients with chronic rhinosinusitis (CRS) after endoscopic sinus surgery, this was reported by Fu, et al 16 and Lee, et al 21 studies. Fu, et al 16 showed that nNO levels was higher in CRSsNP group than that in CRSwNP group.…”
Section: Nno= Nasal Nitric Acid Crswnp= Chronic Rhinosinusitis With mentioning
confidence: 58%
See 1 more Smart Citation
“…They found significantly lower levels of nNO in patients with CRSwNP compared to that in patients with CRSsNP and controls. Conversely, nNO concentrations increased significantly in patients with chronic rhinosinusitis (CRS) after endoscopic sinus surgery, this was reported by Fu, et al 16 and Lee, et al 21 studies. Fu, et al 16 showed that nNO levels was higher in CRSsNP group than that in CRSwNP group.…”
Section: Nno= Nasal Nitric Acid Crswnp= Chronic Rhinosinusitis With mentioning
confidence: 58%
“…Their results revealed that, nNO levels were increased significantly in both groups, and this increasing in nNO levels was related to better quality of life for three months postoperative. At the same time, Lee, et al 21 found a significant increase in nNO levels from baseline to one month and six months postoperatively. Furthermore, Vaidyanathan, et al 20 detected increase in the levels of nNO after two weeks of oral steroid therapy in the CRSNP.…”
Section: Nno= Nasal Nitric Acid Crswnp= Chronic Rhinosinusitis With mentioning
confidence: 82%
“…This bactericidal activity is considered a mechanism of preventing commonly encountered pathogens from excessively proliferating in the sinonasal tract . Interestingly, various studies have described NO levels as a potential biomarker, because the levels in the sinuses are extremely low in patients with CRSwNP, moderately low in patients CRSsNP, and markedly high in healthy patients, increasing after medical treatment and even more after surgery and also correlating with computed tomography (CT) scans and 26‐item SNOT scores …”
Section: Resultsmentioning
confidence: 99%
“…Although surgery has been shown to increase nitric oxide levels, improve quality of life for patients with CRS, and improve long‐term outcomes, the mechanism by which this is achieved is not well understood . There is not yet an established consensus on how potential perioperative therapeutic targets such as bacterial communities, biofilms, mucosal healing, and inflammatory changes should be managed.…”
mentioning
confidence: 99%